Climate radiative feedbacks and adjustments at the Earth's surface. Issue 8 (21st April 2015) - Colman, R. A.
Abstract Climate radiative feedbacks are traditionally defined at top of atmosphere (TOA); however, strong radiative feedbacks also occur at the surface, with profound effect on the surface heat budget and hydrological cycle. "Rapid responses" to radiative forcing also occur and may also be expected to affect the surface. This study evaluates surface radiation changes, using a combined Partial Radiative Perturbation‐Gregory approach, under abrupt increases in CO2 in a climate model. We find significant surface rapid radiative response from changes in clouds, relative humidity, and latent heat flux. As surface temperature increases, strong water vapor feedback exceeds net cooling from atmospheric and surface temperature changes, resulting in increased surface evaporation. Feedbacks from clouds are smaller, with complex horizontal and vertical structures. Surface longwave feedback structures differ widely from those of the TOA and are dominated by lower troposphere changes. Lapse rate, cloud, and albedo feedbacks are small equatorward of around 50° of latitude but stronger at high latitudes. The approach here allows precise evaluation of the rich structure of surface radiative feedbacks.